2015
DOI: 10.3390/molecules20047059
|View full text |Cite
|
Sign up to set email alerts
|

Glycodendrimers and Modified ELISAs: Tools to Elucidate Multivalent Interactions of Galectins 1 and 3

Abstract: Multivalent protein-carbohydrate interactions that are mediated by sugar-binding proteins, i.e., lectins, have been implicated in a myriad of intercellular recognition processes associated with tumor progression such as galectin-mediated cancer cellular migration/metastatic processes. Here, using a modified ELISA, we show that glycodendrimers bearing mixtures of galactosides, lactosides, and N-acetylgalactosaminosides, galectin-3 ligands, multivalently affect galectin-3 functions. We further demonstrate that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 91 publications
1
18
0
Order By: Relevance
“…Mostly, Gal-3 binding was investigated for multivalent ligands based on chemical scaffolds like calixarenes, dendrimers or quantum dots [ 58 , 59 , 89 , 90 , 91 ]. Comparison of our results with findings for these synthetic scaffolds is difficult but can be drawn with regard to the glycan type and number.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly, Gal-3 binding was investigated for multivalent ligands based on chemical scaffolds like calixarenes, dendrimers or quantum dots [ 58 , 59 , 89 , 90 , 91 ]. Comparison of our results with findings for these synthetic scaffolds is difficult but can be drawn with regard to the glycan type and number.…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that Gal-3 assembles as pentamers (via the N-terminal domain) or oligomers (via the C-terminal domain) upon binding to its carbohydrate ligand [ 54 , 55 ]. Thus, multivalent presentation of ligands plays a role in effective binding of Gal-3 [ 56 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…The binding strength of a lectin can be drastically increased by multivalent ligand presentation due to glyco clusters [ 66 , 67 , 68 , 69 , 70 ]. Gal-3 forms pentamers or oligomers during binding events [ 26 , 71 ], and multivalent carbohydrate presentation plays an important role in binding enhancement [ 66 , 72 , 73 , 74 ]. We recently demonstrated enhanced avidity of Gal-3 for multivalent presentation of LacdiNAc-terminated tetrasaccharides as neo-glycoproteins based on BSA [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the interaction of galectin-1 and surface adsorbed multivalent dendrimers 1 – 4 were investigated using an ELISA. The ELISA indicated that galectin-1 binds effectively to the glycodendrimers [ 152 ]. In addition, the binding of galectin-1 to glycodendrimers in solution was investigated using Dynamic Light Scattering (DLS) and Fluorescence Microscopy (FM) [ 89 ].…”
Section: Synthetic Multivalent Systems For Binding Of Galectin-1mentioning
confidence: 99%